Simulation and validation of Airflow Past Hand-Shape Mold Using OpenFOAM - K. Loksupapaiboon (2020)
© Published under licence by IOP Publishing Ltd. This paper aims to present a wind tunnel, aiming to examine the effect of airflow past the hand-shape mold especially airflow around the gap between the fingers of the mold. Part of the aim of this project is to investigate the behavior of airflow past the mold on the different angles, which was valuable to vulcanize rubber glove in the oven. The wind tunnel experiments were performed on the various angle of attack of hand-shape mold from 0 to 180 degrees under the airflow velocity of 5 to 20 m/s. The 3D simulations were carried out by using open source code software, OpenFOAM. The k-? model was used to simulate the turbulent flow past hand-shape mold. The pressure-velocity coupling problem and the convection-diffusion term were solved by using a SIMPLE algorithm and upwind differencing scheme, respectively. The drag force by airflow on the rubber glove mold which obtained by the computational fluid dynamics (henceforth CFD) method was compared with the experimental data. The comparison between CFD simulation and the experimental data showed a fairly close agreement and the average error was less than 13.96%. Further research in this field would be of great help in developing a model to optimize the mold installation inside the rubber glove oven.